Hydrological and geochemical processes constraining groundwater salinity in wetland areas related to evaporitic (karst) systems. A case study from Southern Spain - Gil-Márquez, José Manuel; Barberá-Fornell, Juan Antonio; Andreo-Navarro, Bartolomé; Mudarra-Martínez, Matías (Elsevier, 2017)
Chemical and isotopic evolution of groundwater in an evaporite karst plateau (including wetland areas and saline to hyper-saline springs) located at S Spain was studied. Physicochemical parameters, major ions and stable isotopes were analyzed in rain, brine spring, wetland and leakage water samples, from which the most common mineral saturation indexes were computed and geochemical and isotopic modeling were performed. Results show an apparent relationship between the elevation of brine springs and their water mineralization, indicating that drainage at higher altitude may be associated to gravity-driven flows, since brackish groundwater is isotopically fractionated due to evaporation. On the other hand, the lower altitude springs could drain deeper flows with longer residence time, resulting in highly mineralized and warmer (briny) groundwater. The dissolution of halite and gypsum has proved to be the main geochemical processes, which are favored due by the great ionic strength of groundwater. Calcite precipitation occurs in brackish waters draining wetlands, being boosted by common ion effect (when CaSO4 waters are present) and solute concentration caused by evaporation. Modelling results strongly support the hypothesis that most of the selected springs geochemically evolve in a common (S-N) flowpath. The methods used in this research contribute to a better understanding of the hydrogeological processes occurring in the studied evaporitic system, but also in equivalent hydrological environments worldwide.
Artículo científico publicado en Journal of Hydrology (2017)
Keywords: Aguas subterráneas - Análisis; Evaporite (karst) aquifer; Hydrochemistry; Geochemical modelling/evolution; Stable isotopes; Brine springs